قوامة الزوج بيــن مقـــاصد الشـــــريعة والمستجدات المعــــاصرة Husband's trusteeship between Islamic Law (Shariah) purposes and contemporary time - Abouel Azm, Rehab Soliman; Elsefy, Hossam Eldeen (2017)
This Study dealing with Husband's trusteeship, as a legitimate social psychological issue, trying to highlight the compatibility of practicing with purposes of Shariah in Muslim society, and the impact of those developments on such practices. The researcher chose the subject of the research because of the recent embarkation of Muslim women in the life of the practical and their participation strongly in the financial burdens and spending on some of the basic affairs in the house, Which prompted some women to demand the participation of the husband in his trusteeship, as she shares in spending. The researcher presented the most important evidences on the assignment of men to trusteeship -Not women- And explained in some details the controls of this trusteeship, then touched on those great interests and objectives for which the men were assigned tasks of trusteeship She described how the five necessities can be maintained by a man's trusteeship as original purposes as well as some ancillary purposes, then she talked about the most important reasons why men's trusteeship is compromised, and concluded the research by talking about the reasons for men's trusteeship and contemporary developments. The researcher followed the inductive and analytical method, consulted the scientific references on the research subject, discussed the collected information and analyzed it, and focused on the invocation of the purposes of Sharia in the linkage of information, and strengthening her research with the results and recommendations, And the importance of the subject of the research is reflected in the fact that it touches a law that Allah has assigned to the man which misunderstood and misapplied which affects the stability of Muslim families, and highlights the original purposes side and subordination to the trusteeship of men. Among the most important findings reached by the researcher is that the trusteeship of men is a matter for the Muslim family to preserve religion, soul, offspring, mind and money, As well as it preserves the love, friendship and compassion between the spouses, and emphasizes the need for cooperation on righteousness and piety, Also she found that it is not necessarily that all provisions be affected by contemporary developments, especially if the provision of duty is a mandatory and not permissible, And that there is no objection to the intervention of those responsible to correct the understanding of developments and its bad impact on men and women , controlling the promotion of the media for these developments the way does not suit our venerable legitimacy.